Switching phenomenon in TlGaSe2 layered semiconductor - Seyidov, MirHasan Yu.; Suleymanov, Rauf A.; Balaban, Ertan; Sale, Yasin (Pergamon-Elsevier Science Ltd, 2014)
Electrical switching phenomenon was observed in TlGaSe2 layered ferroelectric-semiconductor applying different types of electrodes on different TlGaSe2 samples in both directions parallel and perpendicular to the pane of the layers. The non-linear current-voltage (CV) characteristics were measured by sweeping the current while measuring the voltage drop and could be classified as current-controlled S-type negative resistance phenomenon. The effects of temperature, illumination and as well as long time annealing within the incommensurate phase on the switching characteristics were also been studied. The switching phenomenon is discussed on the basis of the models widely used for disordered semiconductors. It was shown that TlGaSe2 crystal demonstrates the peculiar behavior that is typical to chalcogenide glassy semiconductors (CGS). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Switching effect; Disordered semiconductors; Ferroelectric-semiconductor; Incommensurate phase